Regulating Medicolegal Death Investigations - Vicks, Antoinette (2019)
Medicolegal death investigators (MDIs) are a crucial part of the death investigation process but the profession remains unregulated and lacks a required accreditation or licensing process that many other professions use. Research shows the current medicolegal death investigations system, though a crucial government function, has existing deficits in its functionality that affect service delivery. The current study was based on an educational theory and utilized open ended survey questions. Data from 16 investigators was collected through surveys where relevant information was asked in the context of their situation and questions were specific to the phenomenon being studied. The data was analyzed by identifying individual and group descriptions of the experience to understand the overall meaning of their experience. The investigators interviewed had different experiences and varying beliefs in the importance of their role as an investigator. They were confident in their roles and provided detailed descriptions of their responsibilities. Additionally, investigators do not appear to have any direct issues due to educational differences but did embrace their roles as death investigators with a desire toward ensuring both their personal safety and that of society. Although many have acquired training as a result of their employment, they did not feel that the lack of prior training was a hindrance. This study contributes to the literature by providing data for consideration when developing regulations promoting standards within the system. This includes the health and safety of medicolegal death investigators and filling the gap of recognizing the need for standardized regulations by identifying the need for uniform training and safety practices